Understanding How Marketing Communication Shapes Purchase Intention: The Case of Herbalife in Tidore - Koja, Nur Akbar A.; Mahifa, Fahria (PT. Sangadji Media Publishing, 2025)
This study investigates the impact of marketing communication on consumers’ purchase intention toward Herbalife products in Tidore. The research was conducted to understand how marketing communication efforts—such as message clarity, credibility, and channel effectiveness—affect consumers’ behavioral intentions in a localized market context. Using a quantitative approach, data were collected through a structured questionnaire distributed to Herbalife consumers in Tidore. A simple linear regression analysis was employed to test the hypothesized relationship between marketing communication and purchase intention. The results revealed a positive but statistically insignificant relationship, indicating that while effective communication contributes to forming consumer awareness and interest, it may not directly lead to purchase intention without the support of other influencing factors such as trust, satisfaction, or perceived product value. Theoretically, the findings reinforce the importance of Integrated Marketing Communication (IMC) principles, which emphasize consistency and credibility across multiple communication channels. Practically, the study suggests that Herbalife distributors should focus on relationship-based communication, transparent product education, and authentic testimonials to build stronger consumer trust and engagement. Limitations of this study include the narrow geographical scope and the use of a single independent variable, which may not capture the full dynamics of consumer purchase behavior.